Dissecting virulence function from recognition: cell death suppression in Nicotiana benthamiana by XopQ/HopQ1‐family effectors relies on EDS1‐dependent immunity. (1st June 2017) - Adlung, Norman; Bonas, Ulla
Summary: Many Gram‐negative plant pathogenic bacteria express effector proteins of the XopQ/HopQ1 family which are translocated into plant cells via the type III secretion system during infection. In Nicotiana benthamiana, recognition of XopQ/HopQ1 proteins induces an effector‐triggered immunity (ETI) reaction which is not associated with strong cell death but renders plants immune against Pseudomonas syringae and Xanthomonas campestris pv. vesicatoria strains. Additionally, XopQ suppresses cell death in N . benthamiana when transiently co‐expressed with cell death inducers. Here, we show that representative XopQ/HopQ1 proteins are recognized similarly, likely by a single resistance protein of the TIR‐NB‐LRR class. Extensive analysis of XopQ derivatives indicates the recognition of structural features. We performed Agrobacterium ‐mediated protein expression experiments in wild‐type and EDS1 ‐deficient ( eds1 ) N . benthamiana leaves, not recognizing XopQ/HopQ1. XopQ recognition limits multiplication of Agrobacterium and attenuates levels of transiently expressed proteins. Remarkably, XopQ fails to suppress cell death reactions induced by different effectors in eds1 plants. We conclude that XopQ‐mediated cell death suppression in N . benthamiana is due to the attenuation of Agrobacterium ‐mediated protein expression rather than the cause of the genuine XopQ virulence activity. Thus, our study expands our understanding of XopQ recognition and function, and also challenges the commonly used co‐expression assays for elucidation of in planta effector activities, at least under conditions of ETI induction. Significance Statement: Many Pseudomonas syringae and Xanthomonas campestris pv. vesicatoria strains are not pathogenic on Nicotiana benthamiana because recognition of the effector proteins HopQ1 and XopQ, respectively, induces effector‐triggered immunity. The comparison of XopQ/HopQ1‐family proteins and characterization of XopQ derivatives indicate that conserved structural features of the protein family are recognized. In transient expression assays, XopQ‐induced effector‐triggered immunity acts efficiently against A . tumefaciens resulting in attenuated bacterial multiplication and transient protein accumulation.